Seismo-petrophysical approach to constrain the lithospheric processes during the continental break-up initiation in the North Tanzanian Divergence, East African Rift - (:unkn) unknown (My University, 2021)
The East African Rift (EAR) is a unique continental open-air laboratory to study the rift evolution, from the beginning of the lithospheric extension in the South, to the oceanisation in the North. The comprehension of rifting processes and evolution are essential to better understand the Earth geodynamic (plate tectonics, mantle plume role, crust-mantle interactions…).In this study, we focus on the North Tanzanian Divergence, which is a rift initiation zone situated at the southern tip of the Eastern Branch of the EAR. There, the rift surface expression results from the interactions between deep-mantle (mantle plume), lithospheric (inherited rheology and stratification, melting...) and crustal (dyke propagation, fault activation...) processes. However, the role of each process on the observed surface activity is still debated, as their respective signals are interlinked. In order to consider the various factors that may interact in this complex zone, a multi-disciplinary study was carried out, combining seismological, petrological and petrophysical approaches.The development of a new hybrid tomographic method for both P and S-body waves permits to image the rift zone with a better resolution (particularly at the Moho depth), the structures boundaries, as well as the mantle plume geometry. My tomographic study points out that the mantle structure limits are consistent with the surface geology (rifting basin, border faults, volcanoes). At a regional scale, the strongest velocity contrasts correspond to the lithospheric inherited structure boundaries (Tanzanian craton and Proterozoic belts), which control the propagation of the rift. The Masai block, south of the NTD, is inferred to have a strong influence in the rift evolution, especially on the volcanism distribution and on the change of the rift morphology. To discriminate which parameters are acting in the rift, the P and S results are combined in a Vp/Vs ratio model. Those images enable us to dete
Keywords: African Research